Axiological Study of the Religious Values of the Longkangan Traditional Pahargyan Tradition in Sumbreng Bay Munjungan Trenggalek - Shofiatul Fariha, Intan (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2025)
This study examines the religious values in the Pahargyan Adat Longkangan tradition in Teluk Sumbreng, Munjungan, Trenggalek, using Max Scheler’s perspective. Pahargyan Adat Longkangan is a ritual ceremony conducted as a form of gratitude by the fishing community for the bountiful results of the sea granted by Allah SWT. This study aims to explore the religious values embedded in this tradition, which reflects the syncretism between local culture and Islamic teachings. Through a qualitative approach and phenomenological analysis, this study finds that the Pahargyan Adat Longkangan tradition contains religious values, including gratitude, sincerity, and acknowledgment of spiritual forces. These values are analyzed using Max Scheler’s hierarchy of values, which includes the values of pleasure, vitality, spirituality, and sanctity. The findings of this research indicate that Pahargyan Adat Longkangan is a manifestation of a culture that blends elements of animism and Islam, serving as a religious expression in the lives of the Teluk Sumbreng community.